Critical Analysis of IARI-Post Office Linkage Extension Model and Strategies for Out-scaling (Indian Journal of Extension Education, 2017)
The evolution in agricultural extension in India for poor public extension system in large diverse farmers community across the country triggered out the ICAR-IARI to conceive an alternate extension approach with Post Office as service partner and KVK as technical partner bridging the two. The present study was undertaken to elicit strength and limitation of the model perceived by stakeholders and suitable strategies for remedies and further development strategies from focus group discussion with stakeholders. The purposive and random sampling technique with 100 beneficiaries farmers (10 from each Branch Post Office) and 60 non-beneficiaries farmers from two districts Sitapur (Uttar Pradesh) and Buxar (Bihar) along with 10 BPMs and 10 KVK scientists from two districts. “Reaching distant farmers” was major strength (Mean=1.608) followed by “timely delivery of seeds” (Mean=1.925) whereas “advisory service through postmaster” was least important strength perceived by stakeholders (n=120). The major constraint was “selection criteria of beneficiary not clear to farmers”(Rank=1) perceived by beneficiaries farmers. Improper information about seed availability was second severe constraint in Sitapur due to the low rate of assurance about seeds availability to different sectors of farmers by branch post master. Biasness of Branch post mater in selection of beneficiaries was reported as second important constraint in Buxar. Lack of incentive was major constraint percieved by BPMs where as manageable problems were recorded from KVK scientists. The use of mass media, ICT, mobile, proper register maintenance, sensitization program, Community Meeting (Gram Sabha) could be integrated into the model for overcoming limiations and further developmental startegies. The replication of the similar mechanism by several ICAR research institutes and SAUs with more improved technologies (inputs and services) can upscale and outscale the model inside the country.